Student Health Service staff, 1963 - Billy Mounts, M.D.::::::::: (1963)
Student Health Service staff of 1963. Back row: Don Curtis, lab; Donna Porter, clerk; Hazel Avery; Mary Shaw, clerk; Vi Hughes, secretary; Li Dye, Physiotherapist; Mary Jo Summers, RN; Eugene Wiggenhorn, Pharmacist. Middle row: Cliff Walker, MD; Val Myers, Clerk; Leona Horvath, clerk; ____; Jeanne Miller, RN; Art James, MD; Barbara Hamonds, lab. Front row: Rhoda Downing, X-ray; Imogene Gow, RN; ____; Billy Mounts, MD, Medical Director; Pat Eilers, RN; Ruth Gran, RN; Florence Messler, RN; Lloyd Hennig, MD.